Marighella multiplicado: a experiência transmídia na biografia e cinebiografia - Camargo, Ralph Willians de (2024)
Transmedia storytelling represents an approach that integrates narrative and media, in which the narrative unfolds across multiple media platforms, which, intertwined, contribute in a distinct and significant way to the whole. This research, in view of this, investigates the relationships about the transmedia storytelling in two media products: Marighella: o guerrilheiro que incendiou o mundo, a biography written by Magalhães (2012), and Marighella, a biopic produced by Moura (2019) based on Magalhães’ book. Both productions portray the figure of Carlos Marighella, an important name in the fight against the military dictatorship in Brazil. The relevance of this research lies in Marighella's significance in Brazilian history and the lack of in-depth academic studies on his biopic. The general objective is to analyze the construction of the transmedia narrative of the biopic and its intrinsic relationship with the biography book, in order to understand how both media portray Marighella, as a fictional character. The specific objectives include studying the theoretical-methodological contribution around the concept of transmedia narrative; contextualizing the figure of Marighella, in order to highlight her space in Brazilian cultural memory; and comparing the media characteristics in the two works. The research is justified by Marighella's relevance in Brazilian history and the lack of in-depth academic studies on her biopic. The theoretical foundation includes studies on transmedia storytelling, based on Jenkins (2009), in addition to its connections with the works of Lévy (1993) and Follain de Figueiredo (2010), which contribute to an analysis of the complex relationships between different media in the context of technological convergence. Based on Augé (1994), the concept of non-place is explored as it allows for reflection on the spaces occupied by transmedia narratives, considering, in this sense, the book itself, a sacred artifact for art, as a medium. In line with Belting (2006), the research addresses the interaction between different media forms and how they exert mutual influence, observing the research corpus through an analytical-comparative method, to analyze the similarities and differences between the works, considering the particularities of each medium. The biography and biopic media are approached based on the considerations of Schwarcz (2013), Burke (1997), Dosse (2009), Bernardet (2010), and Markendorf (2010). Finally, it reflects on the processes of transmedia storytelling and the art of narrating stories in the digital information era, according to Byung-Chul Han (2023). Both the biography and the biopic manifest how different media, in a transmedia approach, converge in portraying the figure of Marighella.